2010
DOI: 10.4174/jkss.2010.78.6.385
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Prophylaxis Using a 2nd Generation Cephalosporin after Laparoscopic Colorectal Resection: A Randomized Trial of 1-day vs. 3-day

Abstract: Purpose:We performed this study to compare 1-day group using a 2nd generation cephalsporin with 3-day group for evaluating hospital acquired infection. Methods: The patients underwent laparoscopic colorectal surgery at Korea University Medical Center Anam Hospital, from August, 2007 to June, 2008. They were randomly allocated to 2 groups: 1-day or 3-day group. A 2nd generation cephalosporin was administered within 1 hour before surgery with 12-hour intervals. In cases of suspected infection, further studies we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…[4][5][6][7] In spite of the longer use of SAP in the present study, some recent randomized controlled trials in Korea have demonstrated that shorter and longer durations of SAP are comparable for preventing SSIs. 27,28 Third, an absence of intraoperative redosing was the other important issue of SAP inappropriateness in the present study. Additional doses of antibiotics are generally recommended if the duration of the surgical procedure is longer than twice the half-life of the antibiotics.…”
Section: Discussionmentioning
confidence: 59%
“…[4][5][6][7] In spite of the longer use of SAP in the present study, some recent randomized controlled trials in Korea have demonstrated that shorter and longer durations of SAP are comparable for preventing SSIs. 27,28 Third, an absence of intraoperative redosing was the other important issue of SAP inappropriateness in the present study. Additional doses of antibiotics are generally recommended if the duration of the surgical procedure is longer than twice the half-life of the antibiotics.…”
Section: Discussionmentioning
confidence: 59%